Orexin Neurons Contribute to Central Modulation of Respiratory Drive by Progestins on ex vivo Newborn Rodent Preparations - Loiseau, Camille; Casciato, Alexis; Barka, Besma; Cayetanot, Florence; Bodineau, Laurence (Frontiers in Physiology, 2019)
Dysfunction of central respiratory CO2/H+ chemosensitivity is a pivotal factor that elicits deep hypoventilation in patients suffering from central hypoventilation syndromes. No pharmacological treatment is currently available. The progestin desogestrel has been suggested to allow recovery of respiratory response to CO2/H+ in patients suffering from central hypoventilation, but except the fact that supramedullary regions may be involved, mechanisms are still unknown. Here, we tested in neonates whether orexin systems contribute to desogestrel’s central effects on respiratory function. Using isolated ex vivo central nervous system preparations from newborn rats, we show orexin and almorexant, an antagonist of orexin receptors, supressed strengthening of the increase in respiratory frequency induced by prolonged metabolic acidosis under exposure to etonogestrel, the active metabolite of desogestrel. In parallel, almorexant suppressed the increase and enhanced increase in c-fos expression in respiratory-related brainstem structures induced by etonogestrel. These results suggest orexin signalisation is a key component of acidosis reinforcement of respiratory drive by etonogestrel in neonates. Although stage of development used is different as that for progestin clinical observations, presents results provide clues about conditions under which desogestrel or etonogestrel may enhance ventilation in patients suffering from central hypoventilation syndromes.